Rare condition of needle tract seeding after EUS-guided FNA for intraductal papillary mucinous carcinoma - Yamabe, Akane; Irisawa, Atsushi; Shibukawa, Goro; Hoshi, Koki; Fujisawa, Mariko; Igarashi, Ryo; Sato, Ai; Maki, Takumi; Hojo, Hiroshi (Endoscopy International Open, 2016)
Background and study aims: We report on a 75-year-old man who was admitted due to pancreatic cystic lesion accompanied by a solid mass with liver metastasis. Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) was performed on the solid mass, and pathological findings revealed the lesion to be an adenocarcinoma diagnosed as intraductal papillary mucinous carcinoma (IPMC). Approximately 3 months after, a cystic subepithelial lesion appeared in the posterior gastric wall where the EUS-FNA had been performed. We performed EUS-FNA again, which revealed that the cystic mass was IPMC with pathology similar to the original lesion. This is a rare case demonstrating needle tract seeding of EUS-FNA for IPMC.